Empowering Siswa SMA Menjadi Agen Perubahan dalam Promosi Pelayanan Kesehatan Digital - Victor E D Palapessy; Rini Susanti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to examine the contribution of historical science in the effort to revitalize museums as educational institutions and preserve cultural heritage. Museums, as public spaces that store and exhibit historical collections, have an important role in facilitating public understanding of the nation's history. However, in the context of the development of the times and changes in public preferences, museums often face challenges in attracting visitors. The contribution of historical science in museum revitalization includes a more interactive approach, technology integration, and storytelling based on in-depth historical research. Thus, historical science not only functions as a source of information, but also as a basis for creating educational experiences that can connect the current generation with relevant historical values. This study suggests various revitalization strategies that can be applied to increase the attractiveness and function of museums as centers for learning and preserving culture, as well as strengthening historical awareness.